Content and practical significance of Radbruch’s formula - Saliger, F. (Інститут держави і права ім. В.М. Корецького НАН України, 2004)
Статья посвящена анализу термина “формула Радбрух” как способа разрешения конфликта между справедливостью и позитивным правом. Исследуются история развития и особенности реализации формулы Радбруха в правовой практике Германии. Автор проанализировал все способы апробации данной формулы на нормативном материале немецкого права. Подчеркнуто, что формула Радбруха рассматривается как основание для возрождения естественного права в Германии. The article is dwells on the analysis of the term “Radbruch’s formula” as the way of solution of the conflict between justice and positive law. The evolution and the peculiarities of realization of Radbruch’s formula in German law practice are under research. The author has analyzed all possible treatments of the formula in German law. It is underlined that “Radbruch’s formula” is considered as the basis of revival of Natural Law in Germany.